MANAJEMEN PELAYANAN PUBLIK PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MAKASAR - Muhammad Taufiq; Taufik Irfadat (Universitas Mbojo Bima, 2022)
This research is descriptive qualitative. The results showed that the services organized by the Makassar City Population and Civil Registration Office were quite effective and efficient, online, accurate, and systematized. The services provided have accommodated the needs of the community regarding legal formal population documents in accordance with legislation number 23 of 2006 concerning population administration, Law number 25 of 2009 concerning public services, Regional Regulation number 9 of 2009 concerning the administration of population administration, and Fitzsimmons' theory in Sinambela et al, McCormick and Tiffin in Dewi Ariani. By applying computer-based technology that has been integrated throughout the territory of Indonesia, coupled with qualified employee competence so that they are able to operate computers to support service and organizational performance to provide services to the community. Through sufficient motivation and work ethic, innovations such as: issuance of population and civil registration cards that are fast, free or free of charge, websites, buss or Mobile Population Registration and Civil Registration Units (UP3SK), technology-based supporting instruments and so on.